Analysis of the effects of anaerobic lactate training on the anaerobic status of elite team handball players - Popovic, J.; Izet, R.; Selimovic, N.; Manic, G.; Miloševic, M. (Sport Science - International Scientific Journal of Kinesiology, 2022)
The aim of this study is to evaluate the effects of a specially designed anaerobic lactate training on the anaerobic status of elite team handball players who have already reached a high competitive level of anaerobic abilities. The hypothesis was that the training will lead to an improvement in anaerobic characteristics for elite team handball players regardless of the high level of abilities they already reached. The research was conducted on a sample of 16 elite team handball players. From the analysis of the results, it can be clearly seen that this training leads to a significant increase in anaerobic characteristics, thus confirming the hypothesis. The mean of an extremely high effect of the training on the increase in all anaerobic characteristics was detected. Enormously large increases in running distances and running speeds in the anaerobic lactate mode cause an enormously high competitive level. Such results were achieved, among other things, owing to a very large increase in the force created and an increase in muscle efficiency, which was also due to an enormous increase in the maximum rate of oxygen consumption (VO2max). The presented and analysed training showed numerous positive features which is why further research is recommended alongside its application in training practice.